FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN CONSUMER GOODS DI BEI - Andriani, Andriani; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACT Dividend is the company retain earning which is shared to the shareholders. The decision in dividend sharing to the shareholders often creates problem between company management and shareholders so it is necessary to notice some factors which influence the dividend sharing. The purpose of this research is to test the influence of quick ratio (QR), return on investment (ROI), debt to asset ratio (DAR), firm size (SIZE), company growth (GROWTH), risk (BETA), free cash flow (FCF), and total assets turnover (TATO) to the dividend policy (DPR). The population is all consumer goods manufaturing companies which are listed in Indonesia Stock Exchange in 2011-2015 periods. The samples collection technique has been done by using purposive sampling technique and 11 companies which have met the criteria with 5 year research periods so the number of the observation is 55 observations. The data analysis technique has been done by using multiple linear regressions analysis. Based on the result of goodness of fit test the models which have been built have met the fit criteria. The result of hypothesis test shows that return on investment, debt to asset ratio and firm size give influence to the dividend policy whereas quick ratio, company growth, risk, free cash flow, and total assets turnover do not give any influence to the dividen policy. Keywords: financial performance, size, risk, free cash flow, dividen policy